Coronary atherosclerosis and risk of acute coronary syndromes in chronic kidney disease using angioscopy and the kidney disease: Improving Global Outcomes (KDIGO) classification. Issue 2 (December 2015) - Kurihara, Osamu; Okamatsu, Kentaro; Mizuno, Kyoichi; Takano, Masamichi; Yamamoto, Masanori; Kobayashi, Nobuaki; Munakata, Ryo; Murakami, Daisuke; Inami, Shigenobu; Ohba, Takayoshi; Hata, Noritake; Seino, Yoshihiko; et al.
Abstract: Objective: This 8-year follow-up cohort study evaluated and compared the degree of coronary atherosclerosis in chronic kidney disease (CKD) according to the Kidney Disease: Improving Global Outcomes (KDIGO) classification using multivessel angioscopy and investigated the impact of the vulnerability of coronary arteries on the relationship between the classification and risk of acute coronary syndromes (ACS). Methods: We studied 89 coronary artery disease patients who underwent angioscopic observation of multiple coronary arteries. The patients were divided into 3 groups: Risk 0, 1, and 2 were equivalent to low risk, moderately high risk, and high and severely high risk, respectively. We examined the frequencies of complex and yellow plaques. Furthermore, we followed all patients for de novo ACS, dividing into two groups according to the existence of vulnerable coronary atherosclerosis (VCA) based on angioscopic findings. Results: The number of yellow plaques per vessel, maximum yellow grade, number of complex plaques per vessel, and cumulative incidence of ACS in all patients were significantly associated with Risk grade progression (p < 0.05 for trend). Among the patients with VCA, Risk 2 had a higher incidence of ACS than Risk0 (p < 0.014) and Risk 1 (p < 0.007), whereas Risk 0 and Risk 1 had similar outcomes. Among the patients without VCA, no de novo ACS events were seen regardless of the Risk group. Conclusions: Coronary atherosclerosis progressed in the early stages of CKD, and once it reached to a vulnerable stage, advanced CKD patients had a synergistically increased risk of ACS. Highlights: The KDIGO classification is associated with coronary atherosclerosis on angioscopy. Vulnerable coronary atherosclerosis worsens the outcomes of advanced CKD patients. Earlier medical therapy should be recommended for CKD patients in the early stage.